(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2022)
This paper aims to desublimate the Kantian sublime starting with the mitigation of the enthusiasm with which some French philosophers have woven its praise. Contrary to what Lyotard and Deleuze argue in their works, in the Analytics of the Sublime Kant does not go beyond himself, nor it is hard to set up a philosophy of the subject after reading these pages. Sublime, for these two clever readers of Kant, is any excessive use of the faculties. But Kant is less interested in excess than in its regulation. Thus, while harmonising with other 80-90s French readings of the Kantian sublime, the faith placed by Lyotard and Deleuze in its potentialities seems unfounded. It is fuelled by a lack of consideration of what happens in the second stage of this complex feeling. Unlike the encounter with the moral law introduced as a ‘fact of reason’ in the Critique of Practical Reason, in the Analytic of the Sublime reason makes itself heard not at the expense of the ego but in support of it. And the ego thus elevated is not only an ego ‘super’. It is a (Freudian) super-ego.